PENYELAM LOKAN DI DESA TANAH REKAH KABUPATEN MUKOMUKO TAHUN (2015-2025) - Nindi Febrianti; Felia Siska (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the community of Lokan divers in Tanah Rekah Village, Mukomuko Regency. The research problem focuses on why many residents became Lokan divers in 2015 and the impact of this livelihood on “the social and economic life of the community from 2015-2025. Lokan diving has been a part of the local community's life since the 1980s and saw a significant increase in 2015, following a decline in the price of Fresh Fruit Bunches (FFB) of oil palm”, which was the community's primary commodity. Lokan diving was chosen as an alternative livelihood because it does not require a large capital, and Lokan has high economic and cultural value in the region. “The research method used is the historical method, with stages including heuristics, source criticism, interpretation, and historiography. Data were collected through observation, interviews with divers, and documentation studies”. The findings indicate that Lokan diving activities have a significant economic and social impact on the community, such as increased daily income and the formation of social solidarity within families and the community. However, since 2022, this activity has begun to decline due to the threat of crocodile attacks in the Selagan River, which has caused fear among the divers.